Phytotoxic Withanolides from Jaborosa rotacea - Nicotra, Viviana Estela (2006)
Twelve new withanolides were isolated from the aerial part of Jaborosa rotacea: five had a spiranoid δ-lactone (1-5); one contained a 26,12-δ-lactone and a C-12-C-23 bond (6); five corresponded to trechonolide-type withanolides with configuration at C-23 opposite of those previously isolated (7, 8, 10-12); two of these have an additional oxido-bridge between C-21 and C-24; finally a withanolide with a hemiketal ring formed between a 21-hydroxyl and a 12-ketone (13) and the closely related jaborosalactone R were also isolated. New compounds were fully characterized by a combination of spectroscopic methods (1D and 2D NMR and MS). The structures of the spiranoid withanolide and of the epimer of trechonolide A were confirmed by X-ray diffraction studies. Compounds 4, 5, 6, and 8 showed selective phytotoxicity toward monocotyledoneous and dicotyledoneous species.